2012
DOI: 10.1080/10236198.2010.510522
|View full text |Cite
|
Sign up to set email alerts
|

Cyclotomic polynomials and minimal sets of Lefschetz periods

Abstract: Let qðtÞ ¼ c n1 ðtÞ· · ·c nk ðtÞ, where c ni ðtÞ is the n i -th cyclotomic polynomial. Let z q ðtÞ ¼ qðtÞð1 2 tÞ 22 or z q ðtÞ ¼ qðtÞð1 2 t 2 Þ 21 , depending if the leading coefficient of the polynomial qðtÞ is ' þ 1' or ' 2 1', respectively. The rational function z q ðtÞ can be written as, the r i 's are positive integers, m i 's are integers and N z is a positive integer depending on z q . In the present paper, we study the set L z :¼ >{r 1 ; . . . ; r Nz } where the intersection is considered over all the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In [17] it was shown that for all orientable compact surfaces without boundary there are C The results of statements (f) and (g) of Theorem 9 also hold for C 1 Morse-Smale diffeomorphisms on orientable compact surfaces without boundary, and their proof are similar, see [17].…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…In [17] it was shown that for all orientable compact surfaces without boundary there are C The results of statements (f) and (g) of Theorem 9 also hold for C 1 Morse-Smale diffeomorphisms on orientable compact surfaces without boundary, and their proof are similar, see [17].…”
mentioning
confidence: 82%
“…In [17] this open question was stated as a conjecture for the C 1 Morse-Smale diffeomorphisms on orientable compact surface without boundary.…”
Section: + T mentioning
confidence: 99%